The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13071626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV Stabilizers on Polypropylene Outdoors

Abstract: Hindered amine light stabilizers (HALSs) and nano ZnO were used to stabilize polypropylene (PP) film-based formulations that were exposed to ultraviolet (UV) light for different lengths of time, simulating the harsh outdoor weather of Dallas, Texas, USA. UV doses applied in our laboratory are 121 times larger than the UV dose provided by the sunlight in Texas. 15 different compositions were studied. Tensile behavior, UV transmittance, thermal stability (by thermogravimetric analysis) and dynamic friction of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Polymers 2022, 14, x FOR PEER REVIEW 5 of additives act as stabilizers, fillers, plasticizers, softeners, lubricants, colorants, flame r tardants, blowing agents, crosslinking agents, and UV absorbers. UV stabilizers are cap ble of reducing the rate of photooxidation of polymeric materials [42]. Various paramete such as color, stability, compatibility, volatility, and cost should be taken into consider tion in the selection of additives.…”
Section: Photostabilization Of Polymers Using Uv Absorbersmentioning
confidence: 99%
“…Polymers 2022, 14, x FOR PEER REVIEW 5 of additives act as stabilizers, fillers, plasticizers, softeners, lubricants, colorants, flame r tardants, blowing agents, crosslinking agents, and UV absorbers. UV stabilizers are cap ble of reducing the rate of photooxidation of polymeric materials [42]. Various paramete such as color, stability, compatibility, volatility, and cost should be taken into consider tion in the selection of additives.…”
Section: Photostabilization Of Polymers Using Uv Absorbersmentioning
confidence: 99%
“…There are three commonly used methods to improve the UV resistance of PU, including the addition of nonreactive anti-UV additives, or anti-UV nanofillers, and using bio-based antioxidant molecules as reaction raw materials. According to the mechanism of action, nonreactive anti-UV additives can be divided into free radical scavengers that can capture active radicals generated during the UV aging of polymers, and UV absorbers that can absorb UV rays. , It has been reported that adding one type of anti-UV additive alone or combining two additives can improve the anti-UV properties of PU. However, the nonreactive anti-UV additives in the PU composites are present in free form, which may migrate during long-term use, significantly affecting the stability and mechanical properties of the composites. Anti-UV nanofillers such as TiO 2 , ZnO, etc., can absorb UV energy by internal electron leap from the valence band to conduction band and convert it to other energy releases with less energy, thus playing the role of UV absorption and shielding. , However, the addition of functional fillers may damage the mechanical properties of the composites and strongly reduce the light transmittance in the visible range, resulting in opaque composites and thus limiting the application scope.…”
Section: Introductionmentioning
confidence: 99%
“…Here, additives could act as plasticizers, stabilizers, crosslinking agents, fillers, blowing agents, softeners, lubricants, flame retardants, colorants, and UV absorbents. These UV stabilizers can minimize the rate of photo-oxidation of polymeric materials [15]. Additive choice is ruled by different factors, such as the desired stability, color, volatility compatibility, and cost.…”
Section: Introductionmentioning
confidence: 99%